2007
DOI: 10.1038/modpathol.3800788
|View full text |Cite
|
Sign up to set email alerts
|

Biliary intraepithelial neoplasia: an international interobserver agreement study and proposal for diagnostic criteria

Abstract: Cholangiocarcinoma of the intrahepatic and extrahepatic bile ducts develops through a multistep histopathologic sequence. Premalignant or non-invasive neoplastic lesions of bile ducts have been historically called biliary dysplasia or atypical biliary epithelium. To this date, no standard terminology or classification system has been offered for these lesions. In 2005, a conceptual framework and diagnostic criteria for biliary intraepithelial neoplasia (BilIN) were proposed using the livers of patients with he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
221
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 264 publications
(226 citation statements)
references
References 27 publications
2
221
0
1
Order By: Relevance
“…10 Intraductal tumors of the extra and/or intra-hepatic bile duct system fulfilling the newly defined diagnostic criteria (see below) were retrieved from the authors' institutional and consultation files and were included in the study. Cases with overt papillary growth or mucinous pyloric gland pattern, small microscopic lesions (not forming tumoral intraepithelial neoplasia), and/or those with MUC5AC expression, e.g., intraductal papillary neoplasms of the bile duct, 9 biliary mucinous cystic neoplasms, 22 biliary intraepithelial neoplasia, 23 as well as intraductal neoplasms of the ampulla were all excluded. 24 …”
Section: Definition Of Intraductal Tubulopapillary Neoplasm Of the Bimentioning
confidence: 99%
“…10 Intraductal tumors of the extra and/or intra-hepatic bile duct system fulfilling the newly defined diagnostic criteria (see below) were retrieved from the authors' institutional and consultation files and were included in the study. Cases with overt papillary growth or mucinous pyloric gland pattern, small microscopic lesions (not forming tumoral intraepithelial neoplasia), and/or those with MUC5AC expression, e.g., intraductal papillary neoplasms of the bile duct, 9 biliary mucinous cystic neoplasms, 22 biliary intraepithelial neoplasia, 23 as well as intraductal neoplasms of the ampulla were all excluded. 24 …”
Section: Definition Of Intraductal Tubulopapillary Neoplasm Of the Bimentioning
confidence: 99%
“…More commonly, biliary intraepithelial neoplasia (biliary dysplasia) evolve into cholangiocarcinoma usually manifesting as an infiltrative tubular adenocarcinoma. 11,21 The other pathway, intraductal papillary neoplasm to invasive cancer, is characterized by a potential progression to both mucinous carcinoma and papillotubular carcinoma, the expression of gastrointestinal markers even in early lesions (adenomas), and a more favourable postoperative prognosis. 11,22 This study suggested that mucinous cystic neoplasm may be a tumour precursor through another route characterized by the least aggressive clinical course and by expression of gastrointestinal molecules during the carcinogenetic process.…”
Section: Discussionmentioning
confidence: 99%
“…As most tumors are unresectable at the time of diagnosis, early detection at a preinvasive stage is the only hope of cure. Two entities are considered to be precursor lesions of cholangiocarcinoma: biliary intraepithelial neoplasia 1 and intraductal papillary neoplasms. 2 Intraductal papillary neoplasms of the bile duct have been recently included in the World Health Organisation classification of bile duct tumors 3,4 and comprise the previous categories of biliary papilloma and papillomatosis.…”
mentioning
confidence: 99%